Epigenetic inactivation of the hsa-miR-203 in haematological malignancies - Chim, Chor Sang (J Cell Mol Med, 2011)
miR-203 is a tumour suppressor microRNA (miRNA). We studied the methylation of hsa-miR-203 in 150 samples including acute myeloid leukaemia (AML), acute lymphoblastic leukaemia (ALL), chronic myeloid leukaemia (CML), chronic lymphocytic leukaemia (CLL) and non-Hodgkin’s lymphoma (NHL) by methylation-specific PCR, and miRNA expression by stem-loop RT-qPCR. hsa-miR-203 promoter was unmethylated in normal controls but homozygously methylated in two AML and four lymphoma cell lines, in which 5-Aza-2′-deoxycytidine treatment led to promoter demethylation and miR-203 re-expression. Restoration of miR-203 expression in lymphoma cells inhibited cellular proliferation and increased cell death, suggesting an inherent tumour suppressor activity. In primary samples, hsa-miR-203 methylation was absent in CML but detected in 5.0% ALL, 10.0% AML, 42.0% CLL and 38.8% of NHL (including six [60.0%] natural killer-cell, nine [40.9%] B-cell and four [23.5%] T cell NHL). Moreover, hsa-miR-203 methylation was associated with hypermethylation of hsa-miR-34a, -124a and -196b in NHL but not CLL. In CLL, hsa-miR-203 methylation was associated with a higher presenting Hb level (P = 0.033). The projected 10 year overall survival of the CLL patients was 58.2%, which was impacted by Rai stage and high-risk karyotypes but not hsa-miR-203 methylation. hsa-miR-203 was more frequently methylated in lymphoid than myeloid malignancies (P = 0.002). In conclusion, miR-203, a tumour suppressor gene, was hypermethylated in a tumour-specific manner with gene silencing. hsa-miR-203 was more frequently hypermethylated in lymphoid than myeloid malignancies. In NHL, hsa-miR-203 methylation was associated with concomitant methylation of other tumour suppressor miRNAs. The frequent hsa-miR-203 methylation in lymphoid malignancies suggested a pathogenetic role of hsa-miR-203 methylation.